Juridical and Sociological Considerations of Judges in Granting Marriage Dispensation after Enactment Law No. 16 Of 2019 - Maimunah Maimunah; Abdul Helim; Noor Aina; Rabiatul Adawiyah (IAIN Manado, 2021)
This research is motivated by many applications for dispensation for Marriage after implementing the latest law related to the age limit for Marriage. This study examines judges' considerations from both normative and social aspects so that this dispensation application can be accepted. This research focuses on 1) how does the Judge review the application for a marriage dispensation after enacting Law Number 16 of 2019 at the Palangkaraya Religious Court? Religion of Palangkaraya?. This empirical research uses a statute approach and Islamic law. The research subjects are 5 (five) judges and 2 (two) informants who are substitute clerks at the Palangkaraya Religious Court. Data were collected through observation, interviews, documentation and analyzed through Islamic Laws and normative. The results of this study indicate that judges in deciding cases of marital dispensation do not only look at the Completeness of the legal administration. But also from a sociological perspective, granting a dispensation application sees aspects of the benefits that must be obtained to avoid more significant damage. The implication is that changes of the law related to marriage dispensation are increasing because it becomes a procedure to complete the marriage administration for underage couples in the provisions of the law.